Customer Concentration, Managerial Ability, and Corporate Performance - Jin, Guanghui; Jiang, Qingjuan; Liu, Xiaolin (Frontiers in Psychology, 2022)
We examine whether and how managerial ability affects the relationship between customer concentrated and corporate performance. Based on a novel measure of managerial ability, we find customer concentration negatively correlates with corporate performance, while managerial ability can mitigate this effect. The negative effect of customer concentration is only significant in the sub-sample of low-ability and lower efficiency in asset utilization, while the moderating effect of managerial ability is significant for all level of asset utilization efficiency, and more prominent for companies with lower gross margin. The results are robust to numerous robustness tests and endogeneity concerns. Further mechanism analysis shows that in addition to superior operating ability, able managers can select customers more beneficial to the firm and reduce the sensitivity of their R&D investment to customers’. These findings indicate that the heterogeneity of managerial ability can play an important role in the supplier-customer context when the supplier firm generally faces one or more concentrated customers.